The Analysis of Figurative Language Used in The Song Lyrics of Adele's Album “30” - I Komang Agus Tri Mahendra; Ni Wayan Suastini; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study analyzes the figurative language used in the song lyrics of Adele’s album “30”. The song writer plays words and language to create attraction and distinctiveness towards the lyric of the song. Figurative language has the ability to be more impactful for the readers. This study is aimed to answer two problems of the study, they are: (1) To identify the types of figurative language used in the song lyrics of Adele's album "30". (2) To analyze the meaning of figurative language found in the song lyrics of Adele's album “30”. The data was analyzed based on the theory of figurative language proposed by Knickerbocker and Reninger (1974) and theory of Meaning proposed by Geoffrey Leech (1974).The result of this study showed there are 7 types of figurative language found in Adele’s album “30”. They are simile, personification, metaphor, synecdoche, hyperbole, irony and paradox. This study found 3 simile, 2 personification, 4 metaphor, 2 synecdoche, 13 hyperbole, 1 irony and 3 paradox. And otherwise in analyzing the contextual meaning this study found some types of meaning used in lyrics of song, those are connotative meaning, thematic meaning, affective meaning, reflected meaning, and stylistic meaning. The data were presented descriptively and formally by using some tables.